Long-term results after reconstruction of full thickness scalp defects with a dermal regeneration template - Faulhaber, Jörg; Felcht, Moritz; Anders, Gloria-Viktoria; Klemke, Claus-Detlev; Wagner, Christina Birgit; Goerdt, Sergij; Koenen, Wolfgang (Journal of the European Academy of Dermatology and Venereology, 2010)
Objective Large scalp defects in which the pericranium has to be resected can be reliably reconstructed using Integra®. In the present study, we retrospectively analysed the long-term outcome of our patients. Methods Nineteen patients were included who had received Integra® dermal regeneration template for treatment of full thickness scalp defects after resection of various malignant tumours. All patients were followed up with a mean follow-up time of 31 months (14-72). Results All transplants were on almost equal levels with the surrounding skin. Cosmetic results were acceptable and scars were stable. Nodal ultrasound status was negative in all patients. During the follow-up period of up to 72 months, no local recurrences were observed. One patient with a leiomyosarcoma received radiotherapy after transplantation. In the irradiated area, multiple small regular-shaped round ulcerations and later on partial necrosis of the transplant occurred when the patient developed renal failure 29 months after the initial operation. Five patients died of disease not related to the primary skin tumour. All other patients are alive and free of disease without any complications. Conclusion After reconstruction of full thickness scalp defects with Integra®, the cosmetic results are appealing and we observed no local recurrences during the follow-up period.